Membrane-associated RING-CH (MARCH) 1 and 2 are MARCH family members that inhibit HIV-1 infection - Zhang, Yanzhao; Tada, Takuya; Ozono, Seiya; Yao, Weitong; Tanaka, Michiko; Yamaoka, Shoji; Kishigami, Satoshi; Fujita, Hideaki; Tokunaga, Kenzo (The Journal of biological chemistry, 2019)
Membrane-associated RING-CH 8 (MARCH8) is one of 11 members of the MARCH family of RING finger E3 ubiquitin ligases and down-regulates several membrane proteins (e.g. major histocompatibility complex II [MHC-II], CD86, and transferrin receptor). We recently reported that MARCH8 also targets HIV-1 envelope glycoproteins and acts as an antiviral factor. However, it remains unclear whether other family members might have antiviral functions similar to those of MARCH8. Here we show that MARCH1 and MARCH2 are MARCH family members that reduce virion incorporation of envelope glycoproteins. Infectivity assays revealed that MARCH1 and MARCH2 dose-dependently suppress viral infection. Treatment with type I interferon enhanced endogenous expression levels of MARCH1 and MARCH2 in monocyte-derived macrophages. Expression of these proteins in virus-producing cells decreased the efficiency of viral entry and down-regulated HIV-1 envelope glycoproteins from the cell surface, resulting in reduced incorporation of envelope glycoproteins into virions, as observed in MARCH8 expression. With the demonstration that MARCH1 and MARCH2 are antiviral MARCH family members as presented here, these two proteins join a growing list of host factors that inhibit HIV-1 infection.